2013
DOI: 10.4141/cjps2012-320
|View full text |Cite
|
Sign up to set email alerts
|

Control of glyphosate-resistant Canada fleabane [Conyza canadensis(L.) Cronq.] with preplant herbicide tankmixes in soybean [Glycine max. (L). Merr.]

Abstract: Byker, H. P., Soltani, N., Robinson, D. E., Tardif, F. J., Lawton, M. B. and Sikkema, P. H. 2013. Control of glyphosate-resistant Canada fleabane [ Conyza canadensis (L.) Cronq.] with preplant herbicide tankmixes in soybean [ Glycine max . (L). Merr.]. Can. J. Plant Sci. 93: 659–667. Glyphosate previously provided excellent control of Canada fleabane; however, with the evolution of glyphosate-resistant (GR) Canada fleabane in Ontario, alternative herbicides must be identified for control of this weed in soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 21 publications
7
35
0
Order By: Relevance
“…Ford et al (2014), recently reported that Canada fleabane demonstrated varying levels of 2,4-D tolerance, which could explain this range in control. For two-way tank mixture of glyphosate + amitrole, Byker et al (2013a) found that control with 900 + 2000 g ai ha −1 at 4 WAT was similar to the current study. For the three-way tank mixtures, the addition of amitrole improved control, compared with the two-way tank mixtures, to greater than 90%, while glyphosate + saflufenacil + 2,4-D controlled GR Canada fleabane to a similar level (Table 2).…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…Ford et al (2014), recently reported that Canada fleabane demonstrated varying levels of 2,4-D tolerance, which could explain this range in control. For two-way tank mixture of glyphosate + amitrole, Byker et al (2013a) found that control with 900 + 2000 g ai ha −1 at 4 WAT was similar to the current study. For the three-way tank mixtures, the addition of amitrole improved control, compared with the two-way tank mixtures, to greater than 90%, while glyphosate + saflufenacil + 2,4-D controlled GR Canada fleabane to a similar level (Table 2).…”
Section: Resultssupporting
confidence: 66%
“…These results were generally consistent with previous studies from our research group which demonstrated that GR Canada fleabane control can vary. For example, Byker et al (2013b) reported control 4 WAT as low as 62% with glyphosate + 2,4-D (900 + 560 g ai ha −1 ); but in a related study, Byker et al (2013a) found that control with glyphosate + 2,4-D (900 + 500 g ai ha −1 ) ranged from 78% to 92% at 4 WAT. Ford et al (2014), recently reported that Canada fleabane demonstrated varying levels of 2,4-D tolerance, which could explain this range in control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations